APLIKASI SISTEM PAKAR DETEKSI KERUSAKAN PADA TELEVISI BERWARNA POLYTRON LED BERBASIS WEB (Information Technology and Telematics, 2013)
Expert system is a system that is designed to mimic the expertise of an expert in answering questions and solving problems. Expert system will provide a solution to a problem is obtained based on dialogue with the user. With the help of someone who is not an expert system expert / expert can solve problems and make decisions that are usually performed by an expert. System development methods used in this study is an expert system that consists of the identification, conceptualization, formalization, implementation, evaluation and development system. System design using the Levelled DFD context diagram and consists of DFD Level 0, Level 1 DFD and ERD. Creating a website using PHP programming and MySQL database.Keywords : Expert System, Polytron LED, PHP, MySQL